Mathematical Model and Modal Analysis of New Type of Circular Arc Tooth Trace Cylindrical Gear - Deng Fayun; Zhang Qi (Jixie chuandong)
The circular arc tooth trace（CATT） cylindrical gear is a new type of gear transmission,which can solve the problem existing in the traditional gears. The dynamic characteristics of the CATT gears are studied with different tool radius and modulus based on the finite element method to reveal its influence on its dynamic characteristics. The accurate 3D model of the CATT gear is established in the UG,and it is imported into the Workbench for the modal analysis of this new type of gear. The simulation results show that,in the case of other parameters are the same,the natural frequency of each order is gradually reducing,the influence of the tool radius on its dynamic characteristics is not significant.